Synthesis and structural characterization of novel new Co (II) complexes of heteroatom bearing ligands - Adiguzel, R.; Sekerci, M.; Tascioglu, S.; Ergin, Z. (My University, 2011)
In this study, the ligands of bis(2-amino-1,3,4-thiadiazole) (L1), bis(2-amino-1,3,4- thiadiazolyl)methane (L2) and bis(2-amino-1,3,4-thiadiazolyl)benzene (L3) have been synthesized via the reactions of oxalic acid (1a), malonic acid (1b) and terephthalic acid (1c) with thiosemicarbazide. The structures of (L1), (L2) and (L3) compounds have been elucidated, by elemental and spectroscopic analyses. Then, novel new Co (II) complexes of (L1), (L2) and (L3) have been synthesized; and the structures of these complexes have been determined by elemental analysis, spectrometric and TGA/DTA methods and magnetic susceptibility and molar conductivity measurements. Coordination numbers of dimeric, L1Co and L2Co complexes and monomeric L3Co complex are found to be six. From the elemental analyses and mass spectra data, the complexes were proposed to the formulas [Co2(L1)(SO4)2(H2O)4]22.5H2O, [Co2(L2)(SO4)2(H2O)4]2.2H2O and [Co2(L3)2(SO4)2(H2O)2].1.5H2O. All complexes were paramagnetic and proposed to be octahedral structure. Molar conductance data revealed that all complexes were non-electrolytes. © 2010 RJPBCS.
Keywords: Bis(2-amino-1,3,4-thiadiazole); Bis(2-amino-1,3,4-thiadiazolyl)benzene and metal complexes; Bis(2-amino-1,3,4-thiadiazolyl)methane